PENGARUH PENGUNGKAPAN MEDIA, KINERJA LINGKUNGAN DAN KEPEMILIKAN SAHAM PUBLIK TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Nugraini, Nur Abfifa; Wahyuni, Wiwik (Jurnal Analisa Akuntansi dan Perpajakan, 2021)
This study aims to examine and analyze the effect of media disclosure, environmental performance and public ownership on disclosure of corporate social responsibility. The data source used is secondary data sourced from annual reports of manufacturing companies published on the Indonesia Stock Exchange website and company websites. The population used is manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The sampling technique used was purposive sampling method. The sample selection criteria are manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2018 period, publishing annual reports in the 2016-2018 period, following PROPER in the 2016-2018 period, and providing the complete information needed by researchers related to variables -research variable. Manufacturing companies that fit the criteria and can be used as research samples are 72. The data collection method is by downloading financial reports and annual reports on the Indonesia Stock Exchange website and searching for the company's website. The data analysis technique used is quantitative analysis method with analysis instruments in the form of descriptive statistical analysis, classical assumption test, multiple linear regression analysis and hypothesis testing.